Influência da competitividade de cromo, cádmio, níquel e chumbo nos parâmetros de transporte de contaminante no solo residual de basalto de Passo Fundo-RS - Santos, Gláucia Carine dos (2010)
The study of the transport of inorganic contaminants in soils is of great importance, especially when considering the risk that contaminants may cause in the quality of surface water and groundwater. Among these inorganic contaminants are toxic metals, which are present in various chemical forms that exhibit different physical and chemical behavior. The understanding the mechanisms of transport and retention of toxic metals permits better understanding of the mobility of these contaminants in soil profiles. The objective of this study is to evaluate the influence of the competitiveness of toxic metals in the transport parameters of contaminants in residual basalt soil of Passo Fundo - RS. Soil samples were collected from experimental field of geotechnical engineering at the University of Passo Fundo to molding specimens. The tests were performed with percolation of solutions containing 5 mg/L toxic metals chromium, cadmium, nickel and lead in monospecie and multispecie solutions, where in the last one, the total concentration was 20 mg/L. The samples were divided into five layers and subjected to the method 3050B-EPA for extraction of the metals. It was possible to find the values of concentration and adsorption present in each layer subjected to this method. The value of dispersivity more appropriate for the tests was obtained by parametric analysis and the value of adsorption for each test was obtained by back analysis. The values of the partition coefficient (Kd) was calculated and compared between tests. The highest retention capacity in monospecie and multispecie tests was showed by chromium. The lowest retention capacity in monospecie test was showed by cadmium and to multispecie test was showed by nickel. The order of selectivity shows a preference for the cadmium retention comparing to lead, when present in multispecie test